2018
DOI: 10.1002/bbb.1947
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of characteristics of grass silage and cattle slurry feedstocks on the cost of methane production

Abstract: Feedstocks characteristics and their provision cost can have a significant impact on the cost of methane production in an anaerobic digestion (AD) facility. This study investigated the impacts of changing grass silage characteristics, grass silage and cattle slurry provision costs and their binary mixing ratios on the cost of methane production from an on‐farm AD facility. The feedstock provision cost contributed about half of the total cost of methane production when the AD facility solely operated on grass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, in regions with less favourable weather conditions, growing this crop can cause issues at planting or harvest and there may also be a negative land use change impact from soil carbon losses if converting former grassland into cropland. Grass silage, although of lower energy value than maize, is easier to integrate into a pasture-based farming system and has been shown to be a suitable alternative under Irish conditions [24].…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…However, in regions with less favourable weather conditions, growing this crop can cause issues at planting or harvest and there may also be a negative land use change impact from soil carbon losses if converting former grassland into cropland. Grass silage, although of lower energy value than maize, is easier to integrate into a pasture-based farming system and has been shown to be a suitable alternative under Irish conditions [24].…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…For example, Xie (2012) reported that maintaining pig manure and grass silage at a ratio of 3:1 yielded 304.2 mL CH 4 /g ml when the two biomass sources were co-digested [16]. In another study, Himanshu et al (2019) reported that maximum synergistic effects for biogas production can be achieved by maintaining a feed ratio of 0.75:0.25 for perennial ryegrass silages with cattle slurry [17]. Both studies observed that increasing the proportion of silage in the feedstock mixture progressively decreased the cost of methane production, increased the methane yield and increased overall plant profitability.…”
Section: Introductionmentioning
confidence: 99%